Secondary hypertension in the pediatric group: a review - Hammes , Bruna; Vita de Souza Diogo , Aguida; Paula Cavalli, Ana; Paula Friedrich, Ana; Peruzzolo Boldori, Beatriz; Sampaio, Erika; Loicono Bettes, Paulo; Buquera Bettes, Julia (Seven Editora, 2023)
Secondary systemic arterial hypertension (SAH) is a potentially curable disease. The pediatric population is the most affected. Due to the lack of deep investigation for secondary causes by health care professionals, many children end up living with the pathology without being diagnosed. Since SAH is a disease that evolves with lesions in several organs, treatment is expected to be carried out early, avoiding chronic health damage. The present research aimed to analyze the underdiagnosis of secondary SAH in children and its repercussion; describe the definition of secondary SAH; identify the main causes of secondary hypertension, and analyze forms of diagnosis and treatment. An integrative bibliographic review of secondary hypertension was carried out in children and adolescents between 2013 to 2022. Twenty-seven studies were chosen for this research. Studies have shown a significant degree of underrecognition of high blood pressure (BP) and hypertension, which is related to the steps needed to determine BP percentiles and the lack of SAH screening in pediatric consultations, which must be done through regular manual measurement of the blood pressure. All children with SAH should be investigated for secondary causes. If the diagnosis is confirmed, treatment of the underlying disease should be done by a specialist. Underdiagnosis of secondary hypertension is still very common since screening is not routinely performed in this age group. Therefore, strategies to improve the acceptance of guidelines should be prioritized. DOI: https://doi.org/10.56238/devopinterscie-117